Taxonomic revision of the Sylvarum group of bumblebees using an integrative approach. Issue 1 (2nd January 2020) - Brasero, Nicolas; Martinet, Baptiste; Michez, Denis; Lecocq, Thomas; Valterova, Irena; Rasmont, Pierre
Abstract : Recent improvements in taxonomy consider multiple operational criteria. Integrative taxonomy provides a methodological framework merging these multisource approaches. Bumblebees are considered as a uniform group where their taxonomy remains one of the most difficult. Here, we investigate the taxonomic statuses inside a monophyletic group including six taxa ( B. inexspectatus, B. mlokosievitzii, B. ruderarius, B. sylvarum, B. velox and B. veteranus ) in the most diverse subgenus of bumblebees: Thoracobombus . We used an integrative approach based on mitochondrial and nuclear genetic markers and eco-chemical traits commonly used in bumblebee taxonomy. For all species, our study shows a clear differentiation in DNA and eco-chemical traits. However, we conserve the subspecies status of B. ruderarius simulatilis and B. sylvarum daghestanicus from the east of Turkey and Iran according to their degree of genetic and eco-chemical differentiation.